Recommended types of texts for bachelor degree foreign language syllabus on the basis of russian state standards for higher vocational education - Svetlana V. Krutskaya; Lilia R. Nurtdinova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This paper addresses the issue of the transition to the two-tier system of higher education in the Russian Federation, consisting of Bachelor and Master degrees. Goals and tasks of foreign language teaching at the first level of higher education - bachelor- are listed. Based on the mentioned goals, tasks, as well as competences, that every Bachelor student should possess, sample lists of texts for teaching all aspect of the language are given. A brief description of each of the four aspects of learning with their distinguishing features is mentioned. A list of the texts required for training each of the types of speech activity (reading, listening, speaking, writing) is given. From the authors’ point of view, these types of texts as much as possible reflect the content of the language education of undergraduates in accordance with Federal State Educational Standard of the third generation. At the end of the article the authors conclude that those professionally oriented sample-texts containing the necessary vocabulary for each of the specialties, designed not only to develop all kinds of speech activity, but also serve as a basis for further self-development of an existing level of foreign language and its application in real-life communication (both business and living environment) of the students and graduates of the Bachelor Degree.